Working with coaches and their teams in youth and collegiate sport in the USA: An interview with Dr Andy Gillham - Commentary - Horn, T. S. (International Journal of Sports Science & Coaching, 2018)
In commenting on this work, I begin by identifying the strengths of this article, especially in terms of what it provides for both researchers and practitioners. This section is followed by a second that identifies a couple of issues to consider for future research and applied work on coaching effectiveness.